Tathbīq Tharīq ah A’rid wa Akhbir ‘alā Mahārah al Kalām - Al Farros, Aathifah; Moenada, Meimunah S (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Purpose- It was a research aiming at finding out the effect of implementing Show and Tell method toward student speaking ability at the eleventh grade of State Islamic Senior High School 1 Pekanbaru. Design/Methodology/Approach- It was an experimental research. Penelitian ini merupakan penelitian eksperimen. All of the the elevent grade of State Islamic Senior High School 1 Pekanbaru were the population of this research, and the sample were the eleventh frade students of Social Science 1 as the experimental group and the students of Social Science 2 as the control group. The subject of this research were students at State Islamic Senior High School 1 Pekanbaru. The object was the effect of implementing Show and Tell method toward student speaking ability at the eleventh grade of State Islamic Senior High School 1 Pekanbaru. Findings- The results of this research are seen from the analysis of the data obtained and conclude that there was an effect of implementing Show and Tell method toward student speaking ability. It was proven from the result of testing the hypothesis by using Mann-Whitney test, the score of Asymp.sig. (2-tailed) 0.000 was lower than 0.05, so H0 was rejected and Ha was accepted. It mean that there was a significant effect of Show and Tell method toward student speaking ability. Research Limitation/Implications- Therefore, from this research it is concluded that the show and tell method can be used in learning Arabic to improve speaking skills.